Can the Halal and CHSE Certificate Improve the Intention Visit to the Restaurant?: Empirical Studies in Halal Restaurant in Tourism Area Lombok Island - rofiqo, azidni; Humaidi, Muchtim (El-Barka, 2024)
This study aims to investigate the effect of CHSE and Halal certification on tourist intentions to visit halal restaurants in the halal tourism area of Lombok Island. It is crucial as it represents the first comprehensive investigation into the interaction between CHSE certification and halal certification in the context of behavioral studies. This study uses a quantitative approach, namely the structural equation model-partial least square with a Likert scale survey with a total of 100 Muslim tourists as respondents. The findings of this study indicate that CHSE certification does not exert a direct influence on intention; however, it does impact intention indirectly through the mediation of trust. In contrast, halal certification demonstrates a significant positive effect on tourist intentions, both directly and indirectly, with trust serving as a mediating variable. This research recommends that the government continue promoting CHSE and halal certification among halal tourism entrepreneurs. Additionally, given the limited sample size of respondents in this study, future research should aim to encompass a broader demographic across Indonesia.